Revisión bibliográfica de técnicas utilizadas para la conservación de frutas y vegetales mediante procesos de osmodeshidratación y ultrasonido - Merchán Baque, Mercedes Inés (2022)
Every day, fruit and vegetables are wasted for various reasons, including the presence of microorganisms such as molds and bacteria that alter the quality of the food. It is also attributed to poor storage management and lack of knowledge to preserve them. For this reason, the purpose of this research is to make known, in a bibliographical way, the applicability of the ultrasound-assisted osmodehydration technique to preserve fruits and vegetables, maintaining the quality of the food. For the investigation, a bibliographical analysis was carried out using the PRISMA method, which consisted of searching for reliable information in databases such as Dialnet, Redalyc, Scielo, ScienceDirect, and other secondary sources, with the theme of ultrasound-assisted osmotic dehydration. Of which, 17 articles were selected for the investigation, whose result was: that the % of ºBrix of the solutions mainly was panela, with a value between 50 - 60%, due to the effect of each one of the matters. Raw materials used, in the same way, the ultrasound frequency used mainly was 40 to 45 kHz (kilohertz), allowing the exchange of dissolved solids and the loss of water. Finally, an ultrasound-assisted osmodehydration study considered variables such as the concentration of solutions used, the temperature, the presence of ultrasound, and the drying at the end of the process to obtain more significant water losses and solid gain